Representations in Intergroup Relations: Reflexivity, Meta-Representations, and Interobjectivity - Wolfgang Wagner; Maaris Raudsepp (Peoples' Friendship University of Russia (RUDN University), 2021)
Social and cultural groups are characterised by shared systems of social objects and issues that constitute their objective reality and their members' identity. It is argued that interpersonal interactions within such groups require a system of comprehensive representations to enable concerted interaction between individuals. Comprehensive representations include bits and pieces of the interactant's representational constitution and potential values and behaviours to reduce possible friction in interactions. On a larger scale, the same is true in encounters, communication, and interaction between members of different cultural groups where interactants need to dispose of a rough knowledge of the other culture's relevant characteristics. This mutual knowledge is called meta-representations that complement the actors' own values and ways of thinking. This concept complements Social Representation Theory when applied to cross-cultural and inter-ethnic interactions.